(untitled) (In situ, 2024)
A field survey was undertaken in February 2023 with the aim of determining the size and boundaries of the previously known Neolithic site of Graduša – Lokve in Islam Grčki, mapping and studying the dark contours visible on aerial photographs and when visiting the site, as well as determining their connection with the distribution of surface finds belonging to the Middle and Late Neolithic. In addition to archaeological artifacts, new insights about the site were gathered and positions were defined for future archaeological excavations at the site.